Personal determinants of mental reliability of an athlete - A.B. Kolosov; N.Yu. Volianiuk; G.V. Lozhkin; N.A. Buniak; V.I. Osodlo (H.S. Skovoroda Kharkov National Pedagogical University, 2019)
Background and Study Aim. Stability of performances at competitions with a preset effectiveness in the presence of sports competition is the result of the reliable functioning of the psyche of an athlete. The hypothesis of the study - mental reliability is associated with certain individual psychological properties, the similarity and difference of which is determined by the level of success of an athlete. The purpose of the study is to identify a set of personality determinants that affect the mental reliability of an athlete. Material and methods. The study involved 58 fencers aged 17-18 years (M = 17.47 SD = 0.53). In this paper, the measurement of the mental reliability of an athlete was carried out using an integral assessment of the success of sports activities developed by E.V. Melnik and E.V. Silich. According to the final success rate, the total sample of the subjects was divided into 2 groups: «successful» and «unsuccessful». For the study of the leading individual psychological properties of the personality, 16-PF multifactor personality questionnaire by R.Kettel was used in the work. The data processing package SPSS was used for data processing. Results. Significant differences were established between the groups of «successful» and «unsuccessful» athletes in the majority of individual psychological properties. The importance of focused analysis and the development of individual mental properties as internal prerequisites for the mental reliability of fencers has been acknowledged. The relationship of personal factors with the success in sports activities is presented. A high level of correlation between the integral indicator of the success of competitive activity and intelligence (factor B), emotional stability (factor C), emotional hardness (I), confidence (O), independence and autonomy (Q2) is revealed. A significant correlation was found between the average level of success in sports and caution (F). This confirms the possibility of applying the methods of research of individual psychological properties of a person when studying the causes of lesions and the prerequisites for the erroneous actions of an athlete. Conclusions . The success of sports activities of fencers does not depend on one individual psychological property of a person. This is the result of a combination of most of them. A greater number of reliable relationships have been revealed between the final indicator of the fencers' success in sports activities and personal factors from the emotional properties group as compared to communicative and intellectual properties groups.